Nonbiological factors affecting outcomes in adolescents and young adults with lymphoma - Dhir, Aditi; Epperla, Narendranath; Costa, Luciano J.; Xavier, Ana C. (Frontiers in Public Health, 2023)
The impact of nonbiological factors (NBF) on survival was investigated in a large cohort of adolescents and young adults (AYA) with lymphoma in the United States (US). We found that uninsured and Medicaid AYA beneficiaries with classical Hodgkin lymphoma (cHL) and non-Hodgkin lymphoma (NHL) are at significantly increased risk of death when compared with their insured counterpart even after adjustment for other factors affecting survival. Increased risk of death was also noted for Non-Hispanic Black (NHB) patients with cHL and NHL when compared to Non-Hispanic White (NHW) patients, however, only Hispanic patients with NHL were found to have a significantly increased mortality risk while those with cHL were not. NHL AYA patients residing in lower-income counties are at increased risk of death. The strong association of NBF with survival indicates opportunities to improve the survival of AYA lymphoma patients by improving access/quality of care in the US.